Confronting poverty : weak states and U.S. national security - Rice, Susan E.; Graff, Corinne; Pascual, Carlos, 1959- (Brookings Institution Press, 2010)
Examines the connection between poverty, fragile states, and transnational conflict and the implications for American security.